Copeptin Concentrations in Plasma of Healthy Neonates in Relation to Water-Electrolyte Homeostasis in the Early Adaptation Period - Anna Jarosz-Lesz; Aniceta Brzozowska; Iwona Maruniak-Chudek (MDPI AG, 2022)
Copeptin (CTproAVP) is a stable by-product of arginine-vasopressin synthesis and reflects its secretion by the pituitary gland, considered as a potential new marker of dehydration. The objective of the study was to investigate CTproAVP measured after the first 48 h of postnatal life in relation to serum effective osmolality, urine osmolality, and vessels filling according to the following variables: delivery mode, postnatal weight loss, fluids administered intravenously to the mother, and fluids given orally to the neonate. A prospective observational study was conducted with 200 healthy term infants (53% male) enrolled. Serum CTproAVP concentrations were measured using the ELISA kit; haematocrit, urine osmolality, serum effective osmolality were assessed after 48 h of life. Sonographic measurements of inferior vena cava (IVC) and aorta (Ao) were performed and IVC/Ao ratios were calculated. No correlations were found between CTproAVP concentrations and both serum effective osmolality and urine osmolality. There was also no association between CTproAVP concentrations and vessel filling represented by IVC/Ao index at 48 h of life.